2013
DOI: 10.1039/c3ra40357b
|View full text |Cite
|
Sign up to set email alerts
|

Specific stress responses to cadmium, arsenic and mercury appear in the metallophyte Silene vulgaris when grown hydroponically

Abstract: The tolerance of the metallophyte Silene vulgaris, a plant suitable for the phytostabilisation of metal(loid)contaminated soils, to arsenic (As), mercury (Hg) and cadmium (Cd) was evaluated in a semi-hydroponic culture system under controlled environmental conditions. The appearance of oxidative stress, alteration of photochemical processes and modification of biothiol content were studied as physiological parameters of metal(loid) stress in plants treated with 0, 6 and 30 mM (As, Hg or Cd) for 7 days. In spit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…The metalloid content in roots was higher than in shoots, showing that more than 97% of the As taken up by peanut plants was retained in the root system. This is a common response of non-hyperaccumulator plants where roots accumulate the major metalloid concentration (Dhankher et al 2006;Carbonell-Barrachina et al 2009;Sobrino-Plata et al 2013). Probably, this toxic level of contaminant inhibited peanut growth, metabolism and transport allowing the passage of the metalloid to shoots disrupting the root protective "barrier" against As(V).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The metalloid content in roots was higher than in shoots, showing that more than 97% of the As taken up by peanut plants was retained in the root system. This is a common response of non-hyperaccumulator plants where roots accumulate the major metalloid concentration (Dhankher et al 2006;Carbonell-Barrachina et al 2009;Sobrino-Plata et al 2013). Probably, this toxic level of contaminant inhibited peanut growth, metabolism and transport allowing the passage of the metalloid to shoots disrupting the root protective "barrier" against As(V).…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes constitutes the major ROS scavenging mechanisms of plants (Mittler 2012) and their induction under different metal (loid) treatments has been demonstrated in several species (Sharma and Dietz, 2009). One of the most studied antioxidant metabolite essential to cope with the oxidative stress induced by toxic elements such as Cd, Hg and As is the tripeptide GSH (Li et al 2006;Bianucci et al 2012;Sobrino-Plata et al 2013). GSH transits from its reduced form (thiol) to its oxidized form (GSSG, disulfide), keeping a strong reducing environment in the cell which plays an important role in…”
Section: Introductionmentioning
confidence: 99%
“…For S. vulgaris, the complexation of toxic ions with organic acids (Harmens et al 1994) or free amino acids (Nadgórska-Socha et al 2009) has been demonstrated. Many experiments have indicated the important role of phytochelatins and glutathione in the response of S. vulgaris to HMs (Nadgórska-Socha et al 2009;Sobrino-Plata et al 2013;Koszelnik-Leszek 2017). Compared to the abundant knowledge on tolerance strategy in S. vulgaris, relatively little is known about the antioxidant machinery preventing oxidative stress which occurred as a consequence of toxic ion penetration into the protoplast.…”
Section: Introductionmentioning
confidence: 99%
“…Strong GR inhibition occurred in roots of cad2-1 ,pad2-1 and rax1-1 treated with 10 μM Hg for 72 h, which also suffered extensive alterations in membrane proteins (i.e., degradation of H + -ATPase and strong inhibition of NADPH-oxidase; Sobrino-Plata et al, 2014b). The GR inhibition appears to be triggered specifically by Hg over certain concentrations inMedicago sativa or Silene vulgaris , whereas other toxic elements usually lead to an enhanced activity (Sobrino-Plata et al, 2013;2009), as can be used as a marker of Hg-stress. Besides the strong GR inhibition, there were minor and non-consistent changes in the proportion of GSSG in the analysed Arabidopsis genotypes (Table 1).…”
Section: Discussionmentioning
confidence: 99%